SINR analysis of FFH/OFDM over frequency selective Rayleigh fading channel - Oturak, Ahmet; Öztürk, Ertan (Wireless communications and mobile computing, 2016)
Fast frequency hopping/orthogonal frequency division multiplexing (FFH/OFDM) has been previously proposed to achieve frequency diversity over frequency selective channels. However, the performances of the FFH/OFDM scheme have been usually calculated using simulations over empirical channel models in earlier works. The main aim of this paper is to theoretically expose the diversity of the FFH/OFDM signal over statistical models, specifically Rayleigh distributed, for frequency selective fading channels. In order to achieve this aim, we first derive the decision variables and the signal‐to‐interference noise ratios of the FFH/OFDM signal at the output of minimum mean square error and zero forcing receivers. For various levels of quadrature amplitude modulation used in FFH/OFDM, the performances are calculated and validated via simulations. The results show that FFH/OFDM in case of zero forcing equalization does not provide any diversity gain even over a frequency selective channel. However, in case of minimum mean square error equalization, it brings significant diversity gain at high signal‐to‐noise ratio (SNR) values with the rise of number of sub‐carriers. Moreover, the FFH/OFDM with four quadrature amplitude modulation scheme provides better performance than that of the conventional OFDM even at low SNR values, as well as a significant diversity gain at high SNR values. Copyright © 2016 John Wiley & Sons, Ltd. We study the performance of the fast frequency hopping/orthogonal frequency division multiplexing (FFH/OFDM) signal over frequency selective Rayleigh fading channel. We derive the decision variables and the signal‐to‐interference noise ratios (SINR) at the output of minimum mean square error (MMSE) and zero forcing (ZF) receivers. The results show that FFH/OFDM does not provide any diversity gain in case of ZF equalization. However, it brings significant diversity gain with the rise of number of sub‐carriers (N) for MMSE equalization.